Bone-Like Multilevel Calcium Phosphate Coating Modulates an Interaction of Mesenchymal Stem Cells and Tumor Cells - Malashchenko V. V.; Shunkin E. O.; Shupletsova V. V.; Khaziakhmatova O. G.; Yurova K. A.; Melashchenko E. S.; Litvinova L. S.; Khlusov I. A. Igor Albertovich; Komarova E. G.; Chebodaeva V. V. Valentina Vadimovna; Sharkeev Yu. P. Yury Petrovich (2019, 2019)
Title screen